Epidemiology of training injuries in amateur taekwondo athletes: a retrospective cohort study - RP Lystad; PL Graham; RG Poulos (Termedia Publishing House, 2015)
The objectives of this study were to estimate the incidence and describe the pattern and severity of training injuries in taekwondo, and to compare pattern and severity of training injuries with competition injuries. One hundred and fifty-two active Australian amateur taekwondo athletes, aged 12 years or over, completed an online survey comprising questions on training exposure and injury history over the preceding 12 months. The main outcome measures were: overall injury incidence rate per athlete-year; training injury incidence rate per athlete-year, per 1000 athlete-training-sessions, and per 1000 athlete-hours of training; injury severity; and injury proportions by anatomical region and by type of injury. Injury incidence rates were calculated with 95% confidence intervals using standard methods, while injury proportions were compared using Fisher's exact test. The vast majority (81.5%) of taekwondo injuries in an average athlete-year occurred during training. The training injury incidence rate was estimated to be 1.6 (95% CI: 1.4, 1.9) per athlete-year, 11.8 (95% CI: 10.4, 13.4) per 1000 athlete-training-sessions, and 7.0 (95% CI: 6.1, 7.9) per 1000 athlete-hours of training. Among athletes with five or fewer injuries, the severity and injury pattern of training injuries were, by and large, the same as for competition injuries. Approximately sixty percent (60.3%) of training injuries required treatment by a health professional. Considering the burden of training injuries exceeds that of competition injuries, taekwondo governing bodies and stakeholders are encouraged to devote more efforts towards the identification of risk factors for, and prevention of, training injuries in the sport of taekwondo.